Preliminary Analysis of the Utilization of PET Plastic Waste in Tourism Areas for Energy Recovery - Iva Yenis Septiariva; Sapta Suhardono; Mega Mutiara Sari; I Wayan Koko Suryawan (Universitas Islam Indonesia, 2022)
Waste management at tourist sites is an unavoidable problem due to the massive number of visitors. One of the types of waste is polyethylene terephthalate (PET) plastic bottles. This study aims to analyze the potential use of PET for waste to energy in tourist areas. This research was conducted in a tourist area in Klungkung Regency, Bali Province. This study only uses grab sampling in measuring waste generation and composition. This research was conducted by proximate analysis and thermal gravimetry analysis (TGA). The measurement of waste generation shows that the PET produced is 1.24 kg/day, or about 43.5% of the total waste generation. Proximate analysis measurements show the value of moisture, ash, volatile, and fixed carbon content, which are 1.53, 0.14, 95.92, and 2.42, respectively. Meanwhile, the caloric value of PET waste is 22.71 MJ/kg. The residue from the TGA results showed 2.575%. The thermal degradation process starts at a temperature of 280ᵒC, and the initial temperature of degradation starts at 406 – and ends at 468ᵒC. Utilization of PET waste at this tourist location can also help the purpose of waste management in Klungkung Regency, namely implementing the Waste to Energy concept at the Local Waste Processing Facility (TOSS).